The politics of salvation: Lukan soteriology, atonement, and the victory of Christ - Reardon, Timothy W. (Library of New Testament studies, 2020)
Preface Acknowledgements Abbreviations -- 1. Defining Spaces: Religion, Politics, and Luke-Acts -- 2. An Inbreaking Salvation (Luke 1:68-79) -- 3. Jesus, Herald of God's Kingdom (Luke 4:18-19) -- 4. Heaven Invading: The Holy Spirit, Church, and Salvific Space (Acts 1-2) -- 5. The Mission of Salvation and Historical Recurrence (Acts 13:16-52) Conclusion Bibliography